PENATAAN BIROKRASI PADA BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN MADIUN - Puspitasari, Novia Ersantia Anggun (Fakultas Ilmu Sosial dan Ilmu Politik, 2014)
Structuring the bureaucracy at the Regional Disaster Management Agency (BPBD) Madiun County is the effort made to organize and prepare organizations and individuals in the BPBDs Madiun. BPBDs Madiun County was formed in 2012 as local governments Madiun County follow the mandate of Law No. 24 Year 2007 on Disaster Management. In addition, the presence BPBDs Madiun County is based on the Regional Regulation No. 15 Year 2011 about Organization and Work Agency for Disaster Management. This research is a qualitative descriptive study using data collection methods of interviews, observation and documentation. The purpose of this research to know how bureaucratic arrangement in BPBDs Madiun County and procedures for filling positions and organizational structure BPBDs Madiun. During the setup process takes place bureaucracies arise several issues including staffing which is still considered according to their expertise, and lack of coordination between BPBDs Madiun with other agencies or institutions related disaster management in the district of Madiun. And the arrangement of the bureaucracy that is driven by the frequency of catastrophic events but there are quite minimal budget for BPBDs Madiun. Based on this, the researchers interested in conducting analyzes using the theory of bureaucracy Arrangement (rightsizing) of Miftah Thoha consisting of three indicators of strategic policy, organizational structure and division of integrating people in the organization. The survey results revealed that the strategic policies in the arrangement of the bureaucracy in BPBDs Madiun County based on Law No. 24 In 2007, Permendagri 46 In 2008, the Regulation No. 15 In 2011 as well as the vision and mission of the Regent of Madiun period of 2009 - 2018 owned by Lack role as Chief Regional Secretary BPBDs due to the absence of clear rules set by the Head BPBDs coordination function. The division of organizational structure on BPBDs done by selecting the type of organizational structure BPBDs type B. As well as in integrating the people in BPBDs Madiun County be based on ability and experience in the field of disaster rather than based on educational background which are owned.Keywords: Reforming the bureaucracy, the Regional Disaster Management Agency Madiun County.